Falta de regulación para la entrega de comodato de bienes inmuebles del sector público en feneficio social - Flores Osorio, Marco Fernando (2014)
This thesis entitled: " LACK OF REGULATION FOR LOAN DELIVERY OF REAL ESTATE PUBLIC SECTOR IN SOCIAL FENEFICIO " . Based on some paperwork Comodato came to realize that it is necessary to analyze real concessions in Comodato , to entities that do not provide social purposes and showed that: In our country , it is not uncommon to see as goods are delivered to the state loan or COMODATO , associations , foundations and sports clubs, many of which have no social purpose , which is why you are given or granted in Comodato goods state indiscriminately, without even requiring the minimum requirements for any particular private or public entity can access a Comodato . 2077. - The Art gives us a definition of Comodato and states that it is " the bailment is a contract in which one party delivers to the other free kind , movable or root, to make use of it, with return by the same species after completion of use. " The fact that this article states what is the loan, but not indicating who may be beneficiaries , does not provide the statement of the purpose or object to be given to these goods and for this reason, from my point of view are becoming misuse them .We see in particular, which are the municipalities of our country , who granted goods Comodato to work in sports clubs and complexes, which do not provide social benefits , in contrast , are only contributing to the enrichment of certain group of people with the best same political guidelines by making use of free goods and for long periods. But I think that ordinary people we could not do creditors of these luxuries , as we have to work very hard to deprive us of many tastes , save and borrow to be able to buy a property, when other groups of people with more influences get to be granted assets without paying anything even municipalities , only offering that " shall be returned in the same condition that they gave when finished use " This is unprecedented , while the common citizen as we work and pay our council tax we have to endure that state assets which by the way are the people people who get economic returns from the use of these goods, but also for the outrageous debts with the Internal Revenue Service and their workers are delivered to which he did not pay them for long periods , nor cancel debts to its creditors , who follow the same legal action in the courts to enforce their rights . These are all goods and qu7e are the Ecuadorian State , of which some groups enjoy and profit purposes especially to governments. For this and for many abuses , I have seen the need to provide with my thesis , since it is necessary that the Civil Code regulate more effectively the Comodato split using mostly public goods and should be with a social order , it is common to see that municipalities are delivering goods left and rigwithouteven knowing what purpose will have them or if they are the right people who manage . Therefore this study is aimed to seek an amendment to the Civil Code , where essential to the provision of goods COMODATO requirements are incorporated , as well as who are natural persons or legal game tries to provide social benefits to the community with these goods, for I have seen that these properties are awarded to resorts to particular group or association , gymnasiums , stadiums . But never talk of creating community nurseries with qualified and specialized personnel that we can access at low cost , or maybe soup kitchens for people who need it, the latter is known that if there are but few . The state according to the Constitution of the Republic and the National Plan for Good Living , should give these goods to Day Hospitals , state-funded , community pharmacies with generic drugs , places of accommodation to people who do not have to be created where and in order to do so , there are many social purposes that many public goods that are left will be given, such as the IESS who owns many buildings that do not offer any services that keep furniture that is impaired by not giving any use for the benefit of foundations or schools if they need these goods. We are tired of all these things despite many complaints by councilors who also disagrees with these bailment to the goods delivered are many many for-profit and a few that are mentioned below are the only ones with den social purposes